Bucharest city urban groundwater monitoring system. (2017) - Gaitanaru, Dragos; Gogu, Constantin Radu; Boukhemacha, Mohamed Amine; Litescu, Liviu; Zaharia, Valentin; Moldovan, Alexandru; Mihailovici, Madalin J.
Abstract: Bucharest City is the capital of Romania and also the biggest city. Situated in an alluvial plane, the geological settings are represented by a series of overlaying Quaternary strata of aquifers and aquitards. Some of these aquifers are used for water supply (the deeper aquifers) and the shallow and medium ones are characterized by an intense interaction with the urban infrastructure. The paper presents the drivers and also the architecture of the urban groundwater monitoring systems developed in the last years in order to observe the urban impact upon the first two aquifers layers. The anatomy of the system is correlated with the urban infrastructure. Also the paper presents the future monitoring system that will be develop within a European JPI project.